Islamic Republic of Afghanistan : Sixth Review Under the Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver of Nonobservance of a Performance Criterion, Modification and Performance Criteria, and Rephasing and Extension of the Arrangement. (IMF Staff Country Reports; Country Report, 2010)
This paper examines Afghanistan's Sixth Review under the arrangement under the Poverty Reduction and Growth Facility. The growth of currency in circulation has been carefully managed to support the decline in inflation from double-digit levels in 2008. Reserve money, however, has been volatile, primarily because of unexpected changes in coalition forces' deposits. Money demand remained strong as evidenced by the decline in inflation and a nominal appreciation of the Afghani. The authorities have also been implementing a short-term revenue action plan with measures aimed at limiting corruption.